2010
DOI: 10.1590/s1415-47572010005000041
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of IRAP and ITS-RFLP marker systems in accessing genetic variation of Pyrenophora graminea

Abstract: The usefulness of IRAP (inter-retrotransposon amplified polymorphism) and ITS-RFLP (restriction of PCR-amplified internal transcribed spacers of the rDNA) markers in the analysis of 39 Pyrenophora graminea isolates was determined. Each marker system could discriminate between all of the isolates in detecting polymorphism, albeit with variable efficiency. IRAP and ITS-RFLP produced 85% and 77% polymorphic bands, respectively, with a corresponding mean polymorphic information content (PIC) of 0.38 and 0.36. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 24 publications
(26 reference statements)
1
19
0
Order By: Relevance
“…The genetic variability of pathogenic populations has been analyzed using several different molecular markers (Zein et al, 2010;Nusaibah et al, 2011). The most commonly used marker techniques include inter-simple sequence repeat (ISSR) analysis, which has been widely used to study fungal variability (Neal et al, 2011), and the analysis of inter-retrotransposon amplified polymorphisms (IRAPs), which is a readily accessible method owed to the availability of sequencing databases and the abundance of retrotransposons in the genomes of many organisms (Zein et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The genetic variability of pathogenic populations has been analyzed using several different molecular markers (Zein et al, 2010;Nusaibah et al, 2011). The most commonly used marker techniques include inter-simple sequence repeat (ISSR) analysis, which has been widely used to study fungal variability (Neal et al, 2011), and the analysis of inter-retrotransposon amplified polymorphisms (IRAPs), which is a readily accessible method owed to the availability of sequencing databases and the abundance of retrotransposons in the genomes of many organisms (Zein et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Arabi and Jawhar (2007) observed high genetic diversity in Syrian population of P. graminea with ITS region. Zein et al, (2010) observed fingerprints generated www.intechopen.com from the five restriction digestions of the nrDNA ITS region denoted high levels of intraspecific variation within the P. graminea population. Bakri et al, (2011) observed high levels of intraspecific variation within the P. graminea population.…”
Section: Internal Transcribed Spacer Regions (Its)mentioning
confidence: 96%
“…Isolates of different species of have been characterized used this methodology (Arabi & Jawhar, 2007;Wu et al, 2003;Zein et al, 2010). This procedure was developed by Botstein et al, www.intechopen.com (1980).…”
Section: Restriction Fragment Length Polymorphism (Rflp)mentioning
confidence: 99%
See 2 more Smart Citations